Kinematic Distance of Galactic Radio Objects. Issue Volume 9:Issue S297(2013) (21st February 2014) - Zhu, H.; Tian, W.; Su, H.; Wu, D.
Abstract: We briefly summarize the method of kinematic distances of Galactic radio objects and discuss the ambiguity in this method. Both Hi absorption and Hi self-absorption are effective tools to solve the kinematic distance ambiguity. We build the 21 cm Hi absorption spectrum of the complex G35.6-0.5, and suggest SNR G35.6-0.4, one component of the complex, is located at the near side distance of about 3.6 kpc.